Body Mass Index Is Associated With All-cause Mortality After THA and TKA. Issue 6 (June 2018) - Dowsey, Michelle M.; Choong, Peter F. M.; Paxton, Elizabeth W.; Spelman, Tim; Namba, Robert S.; Inacio, Maria C. S.
Abstract: Background: Both obesity and underweight are associated with a higher risk of mortality in adulthood, but the association between mortality after arthroplasty and extreme ranges of body mass index (BMI) have not been evaluated beyond the first year. Questions/purposes: The purpose of this study was to investigate the association between BMI and all-cause mortality after TKA and THA. Methods: Data from two arthroplasty registries, the St Vincent's Melbourne Arthroplasty (SMART) Registry from Australia and the Kaiser Permanente Total Joint Replacement Registry (KPTJRR) from the United States, were used to identify patients aged ≥ 18 years undergoing elective TKAs and THAs between January 1, 2002, and December 31, 2013. Same-day bilateral THA and hemiarthroplasties were excluded. All-cause mortality was recorded from the day of surgery to the end of the study (December 31, 2013). Data capture was complete for the SMART Registry. No patients were lost to followup in the KPTJRR cohort and 2959 (5%) THAs and 5251 (5%) TKAs had missing data. Cox proportional hazard regression was used to estimate the all-cause mortality associated with six BMI categories: underweight (< 18.5 kg/m 2 ), normal weight (18.5-24.9 kg/m 2 ), overweight (25.0-29.9 kg/m 2 ), obese class I (30.0-34.9 kg/m 2 ), obese class II (35.0-39.9 kg/m 2 ), and obese class III (> 40 kg/m 2 ). For TKA, the SMART cohort had a median followup of 5 years (range, 0-12 years) and the KPTJRR cohort had a median followup of 4 years (range, 0-12 years). For THA, the SMART cohort had a median followup of 5 years (range, 0-12 years) and the KPTJRR cohort had a median followup of 4 years (range, 0-12 years). Results: In both the Australian and US cohorts, being underweight (Australia: hazard ratio [HR], 3.72; 95% confidence interval [CI], 1.94-7.08; p < 0.001 and United States: HR, 1.88; 95% CI, 1.33-2.64; p < 0.001) was associated with higher all-cause mortality after TKA, whereas obese class I (Australia: HR, 0.66; 95% CI, 0.47-0.92; p = 0.015; United States: HR, 0.71; 95% CI, 0.66-0.78; p < 0.001) or obese class II (Australia: HR, 0.54; 95% CI, 0.35-0.82; p = 0.004; United States: HR, 0.73; 95% CI, 0.66-0.81; p < 0.001) was associated with lower mortality when compared with normal-weight patients. In the US cohort, being overweight was also associated with a lower risk of mortality (HR, 0.76; 95% CI, 0.71-0.82; p < 0.001). In the US cohort, being underweight had a higher risk of mortality after THA (HR, 2.09; 95% CI, 1.65-2.64; p < 0.001), whereas those overweight (HR, 0.73; 95% CI, 0.67-0.80; p < 0.001), obese class I (HR, 0.68; 95% CI, 0.62-0.75; p < 0.001), or obese class II (HR, 0.71; 95% CI, 0.62-0.81; p < 0.001) were at a lower risk of mortality after THA when compared with normal-weight patients. In patients undergoing THA in the Australian cohort, we observed no association between BMI and risk of death. Conclusions: We found that even severe obesity is not associated with a higher risk of death after arthroplasty. Patients should be informed of this when considering surgery. Clinicians should be cautious when considering total joint arthroplasty in underweight patients without first considering their nutritional status. Level of Evidence: Level III, therapeutic study.